2002
DOI: 10.1029/2001jd001248
|View full text |Cite
|
Sign up to set email alerts
|

A 3‐year record of simultaneously measured aerosol chemical and optical properties at Barrow, Alaska

Abstract: [1] Results are presented from 3 years of simultaneous measurements of aerosol chemical composition and light scattering and absorption at Barrow, Alaska. All results are reported at the measurement relative humidity of 40%. Reported are the annual cycles of the concentration of aerosol mass, sea salt, non-sea-salt (nss) sulfate, methanesulfonate or MSA À , NH 4 + , and nss K + , Mg +2 , and Ca +2 for the submicron and supermicron size ranges. Submicron nss SO 4 = , NH 4 + , and nss K + , Mg +2 , and Ca +2 pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

35
410
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(456 citation statements)
references
References 54 publications
35
410
3
Order By: Relevance
“…8b. The monomodal accumulation-mode aerosol is characteristic for the Arctic haze, which mainly consists of POM and sulfate (Quinn et al, 2002). Single particle analysis of aerosol particles samples taken at the Zeppelin Observatory, Svalbard, that occurred before the transition to the Arctic summer showed a dominance of spherical organic-like particles in the submicrometer range with an Eurasian influence (Behrenfeld et al, 2008).…”
Section: Pscf Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…8b. The monomodal accumulation-mode aerosol is characteristic for the Arctic haze, which mainly consists of POM and sulfate (Quinn et al, 2002). Single particle analysis of aerosol particles samples taken at the Zeppelin Observatory, Svalbard, that occurred before the transition to the Arctic summer showed a dominance of spherical organic-like particles in the submicrometer range with an Eurasian influence (Behrenfeld et al, 2008).…”
Section: Pscf Analysismentioning
confidence: 99%
“…Hence the so-called Arctic haze can be trapped for 15 to 30 days (Shaw, 1981(Shaw, , 1995. The major part of the Arctic haze consists of particulate organic matter (POM) and sulfate but also contains ammonium, nitrate, mineral dust, black carbon and heavy metals (Quinn et al, 2002). Reported PNSDs show an accumulation mode with N CN constantly increasing during the winter months from October until April from below 50 to above 200 cm −3 (Tunved et al, 2013).…”
mentioning
confidence: 99%
“…For this purpose, an evaluation of the mass fractions of the main particulate chemical components was performed, by taking into account the results found by Quinn et al (2002), who examined a 3-year set of simultaneous measurements of aerosol chemical composition and light scattering and absorption measurements performed at Barrow from October 1997 to December 2000, for rather low relative humidity conditions. These estimates were given by Quinn et al (2007) in terms of monthly mean concentrations of aerosol mass constituents, such as sea salt, non-sea salt (nss) sulphate, methane sulphonic acid (MSA), ammonium ions, and nss K, Mg and Ca ions, for both the submicron and supermicron size ranges.…”
Section: Arctic Aerosol Radiative Propertiesmentioning
confidence: 99%
“…Several studies, 10 as early as the 1980s, reported a distinctive seasonal cycle in the Arctic aerosol and BC concentration and visibility (Barrie, 1986;Quinn et al, 2007;Rosen et al, 1981;Schnell, 1984;Wang et al, 2011). The so-called Arctic Haze phenomenon in the winter-spring period has been attributed to increased levels of transported Particulate Matter (PM) from anthropogenic emission sources at lower latitudes and slower wet deposition removal processes (Barrie et al, 1981;Law and Stohl, 2007;Quinn et al, 2002Quinn et al, , 2007.…”
mentioning
confidence: 99%